RETRACTED: Oral Administration of Brain Protein Combined With Probiotics Induces Immune Tolerance Through the Tryptophan Pathway - Hou, Yongxin; Xu, Lixia; Song, Sirong; Fan, Weijia; Wu, Qiaoli; Tong, Xiaoguang; Yan, Hua (Frontiers in Molecular Neuroscience, 2021)
Excessive inflammation leads to secondary immune damage after traumatic brain injury (TBI). The intestinal mucosa is a key component of immune tolerance due to gut-brain axis regulation, but the curative effect is not optimal. Intestinal dysfunction impairs the establishment of immune tolerance in patients with TBI. Therefore, we orally administered brain protein (BP) combined with probiotics to induce immune tolerance and explored the mechanism by which the homeostasis of the microbiota contributes to the enhancement of curative effects by BPs. Herein, we demonstrated that patients with TBI and surgical brain injury (SBI) models of rats had obvious dysbiosis. Notably, the intestinal barrier, proinflammatory cytokines, and activation of microglia demonstrated that excessive inflammatory damage was better controlled in the combined group (oral administration of BP combined with probiotics) than in the BP group (oral administration of BP). Fundamentally, tandem mass tag (TMT)-based quantitative proteomics analysis revealed that BP and probiotics preferentially affect Try-related pathways. A series of experiments further confirmed that Indoleamine 2,3 dioxygenase (IDO)/Kynurenine (Kyn)/Aryl hydrocarbon receptor (AhR) expression was high in the BP group, while Tryptophan hydroxylase 1(TpH1)/5-hydroxytryptamine (5-HT) only changed in the combined group. This study suggests that probiotics can enhance the efficacy of oral BP-induced immune tolerance through the Try pathway.